Babi Yar: da história à poesia e à música - Rudka, Anastasia (2022)
The present dissertation will have as object of study both the interlinguistic translation into English and Portuguese, as well as the intersemiotic translation of the poem “Babi Yar” written by the poet Yevgeny Yevtushenko. The poem was inspired by the story of one of the biggest massacres of Jews and civilians by the Nazi troops, which took place in the city of Kiev during the World War II. Thus, our first objective, when talking about the real facts that were the basis for the creation of the poem, is to conclude how much the poem is, in fact, an intersemiotic translation, in the broad sense of the term, of the tragedy that then took place in the Babi Yar’s ravine. After a brief analysis of the life and work of the author Yevgeny Yevtushenko, we propose a commented translation into Portuguese of the poem, with a comparative analysis being made with its translation into English by Benjamin Okopnik (1996). The aim of this analysis is to conclude on the problems inherent to poetic translation. With the analysis of the intersemiotic translation of the poem by Dmitry Shostakovich (Symphony No.13) we intend to conclude on the potentialities and limits of intersemiotic translation, namely as a codification and aesthetic representation of the Holocaust. In this research and translation analysis work, we rely on the theories of authors such as Julio Plaza, Susan Bassnett, Umberto Eco and Jean-Paul Vinay & Jean Darbelnet to support our opinions and conclusions.